(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
​ In the article the processes of development of motivation in the context of age development of the personality of adolescents are considered. The issues of personal and professional self-determination in adolescence are explored. The role of motivation in its structure is determined. The typology of professions is considered. The adolescence as an important transitional period in the development of motivation to professional self-determination is explored. The results of the empirical study of the characteristics of the motivation of modern adolescents to choose a profession, in particular, on account of the complex of their cognitive interests, are presented. Psychological and pedagogical references for teachers and parents concerning development of motivation for professional self-determination of adolescents are developed.